Maternal Factors Associated with Low Birth Weight Babies (Medical Forum Monthly, 2024)
Objective: To determine the maternal factors associated with low birth weight babies in women age of 15-35 years.Study Design: Case control study.Place and Duration of Study: This study was carried out in the department of gynecology and obstetrics, Isra University Hospital (IUH) Hyderabad, Sindh from 02-05-2009 to 02-11-2009.Materials and Methods: Total 200 women were included in the study.100 as cases and 100 as control. Mothers aged 15-35 years, who deliver live or dead singleton baby through vaginal delivery or cesarean section after 37 week of gestation were included in the study while others who have delivered newborn with congenital abnormalities, had multiple pregnancy or known chronic illness (hypertension, tuberculosis, diabetes mellitus) were excluded from the study.Results: The mean + SD of maternal age (years) in cases was26.40 + 4.77 and controls was 26.23 + 4.36 with P-value 0.739. The mean + SD of maternal weight (Kg) in cases was 53.13 + 8.93 and in controls was 64.97 + 13.72 with P-value < 0.001.Maternal history of smoking and anemia had significant association with low birth weight with P-Value of 0.005 and <0.001 respectively. Conclusion: It was concluded from our study that malnutrition, anemia, short stature like under weight & height are important risk factors for low birth weight.